(untitled) (Journal of Rangpur Medical College, 2026)
Background: The clinical shift from non-alcoholic fatty liver disease (NAFLD) to metabolic dysfunction-associated steatotic liver disease (MASLD) emphasizes identifying modifiable drivers of fibrotic progression. While obesity and diabetes are established risk factors, the independent impact of sleep duration on the "velocity" of liver stiffness measurement (LSM)-the longitudinal rate of change-remains poorly characterized. Objective: This study aimed to quantify the 5-year relationship between sleep duration and liver stiffness velocity. Methods: We conducted a prospective cohort study of 1,076 participants in Bangladesh (Dhaka, Rangpur, Sylhet) from 2020 to 2025. Baseline and 5-year liver stiffness were measured using vibration-controlled transient elastography (VCTE). Sleep duration was assessed via the Pittsburgh Sleep Quality Index (PSQI). Multivariable regression and causal mediation analysis evaluated the impact of sleep on LSM change (Δ LSM). Results: Over 5 years, 19.7% of individuals were Progressors. Multivariable regression established sleep duration as a potent independent predictor of liver stiffness velocity (β=-0.20,95% CI: -0.28, -0.12, p<0.001), while BMI was not a significant longitudinal driver in adjusted models. Mediation analysis confirmed a significant direct effect of sleep on Δ LSM (ADE=-0.19, p<0.001), with negligible mediation by BMI. Survival analysis showed that individuals sleeping ≤6 hours had a significantly higher hazard for reaching advanced fibrosis compared to those sleeping ≥6 hours. Conclusion: Short sleep duration is a direct, primary driver of liver stiffness velocity in MASLD. Restorative sleep (≥7 hours) is associated with stability and is a prerequisite for fibrosis regression. Addressing sleep hygiene is a critical, independent therapeutic target for preventing advanced liver disease. J Rang Med Col.2026 Mar;11(1): 159-165